The itinerary of families with children from 0 to 6 years of age in the search for health care. Preview Note - Pamela Camila Fernandes Rumor; Márcia Grisotti; Adalbi Cilonei Souza; Astrid Eggert Boehs (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
Exploratory study with quanti-qualitative approach which aims to identify and to analyze the itinerary of low income families in the search for health care of children from 0 to 6 years of age, in two neighborhoods in the city of Florianópolis. The theoretical framework approaches the care system as a cultural system, identifying and analyzing the several care subsystems: popular, familiar and professional. After being approved by the ethics committee, the research is in the phase of data collection: interviews with mothers in different places as daycare centers, meetings of associations and churches.